2020
DOI: 10.1038/s41416-020-0884-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-622 is a novel potential biomarker of breast carcinoma and impairs motility of breast cancer cells through targeting NUAK1 kinase

Abstract: Background Aberrant expression of microRNAs (miR) has been proposed as non-invasive biomarkers for breast cancers. The aim of this study was to analyse the miR-622 level in the plasma and in tissues of breast cancer patients and to explore the role of miR-622 and its target, the NUAK1 kinase, in this context. Methods miR-622 expression was analysed in plasma and in tissues samples of breast cancer patients by q-RT-PCR. Bioinformatics programs, luciferase assay, public d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 83 publications
2
17
1
Order By: Relevance
“…In recent years, miR-622 has emerged as one of the most promising tumorsuppressive microRNAs, which is underscored by numerous studies addressing its potent role in diverse types of cancer [ 13 , 17 , 18 , 20 , [38] , [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miR-622 has emerged as one of the most promising tumorsuppressive microRNAs, which is underscored by numerous studies addressing its potent role in diverse types of cancer [ 13 , 17 , 18 , 20 , [38] , [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated by our group and others that microRNAs (miRs) represent powerful small RNA molecules that modulate drug resistance related features in HCC [ 10 , 24 ]. In recent years, miR-622 has emerged as one of the most promising tumorsuppressive microRNAs, which is underscored by multiple studies addressing its potent role in diverse types of cancer [ 6 , 10 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the most interactions are between the mRNAs KRAS, AKT1, SNAI2, and miR-NAs including hsa-mir-637, hsa-mir-622, and hsa-mir-545 in this network. The vital role of these mRNAs and miRNAs hsa-mir-637, hsa-mir-622 in BC has been previously revealed [23][24][25][26][27]. The hsa_circ_0003028/ miRNA/mRNA network also contained 1cir-cRNA, 22 miRNAs, and 78 mRNAs (Fig- Transcription factor products of the mRNA member of the evaluated circRNA/miRNA/ mRNA networks We found that the mRNAs with having the transcription factor role involved in the predicted regulatory hsa_circ_0013958/miRNA/ mRNA network were SNAI2 and SP7.…”
Section: Potential Circrnas-mediated Sponge Regulatory Networkmentioning
confidence: 97%